Parody and carnivalization in the Luis Buñuel`s play Hamlet - Guevara Aguirre, Dayanara (2021)
This article proposes an analysis of Luis Buñuel’s play Hamlet. The analysis is done from Mijaíl Bajtín’s main concepts of the Carnival Theory: popular culture, carnivalization, grotesque and laughter. It represents a contribution to the lacking knowledge around a marginal text in the scope of literary criticism as well as drama criticism. It states that Buñuel’s play is an ambivalent, open, intertextual, irreverent and parodic text.